2017
DOI: 10.1016/j.jvscit.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel, non-gadolinium-enhanced magnetic resonance imaging technique of pedal artery aneurysms

Abstract: Non-gadolinium-enhanced magnetic resonance angiography (nMRA) is a noninvasive, contrast-free imaging modality used for visualizing pedal arterial anatomy. We report application of the nMRA technique for detailed arterial imaging in a patient with dorsalis pedis aneurysm. Compared with digital subtraction angiography, we demonstrate that nMRA provides sufficient arterial detail needed to develop a complex operative plan before vascular intervention without risk of contrast agent or ionizing radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Unlike earlier flow‐sensitive preparation pulses used for subtractive angiography methods, the Fourier‐based VS preparation offers flexible velocity pass‐ and stop‐bands and sharp transition between the 2 bands and therefore enables positive angiographic contrast using single acquisition without subtraction. Although developed for renal angiography for its first application, VS‐MRA has shown great promise for peripheral, cerebral, and pedal angiography as well …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike earlier flow‐sensitive preparation pulses used for subtractive angiography methods, the Fourier‐based VS preparation offers flexible velocity pass‐ and stop‐bands and sharp transition between the 2 bands and therefore enables positive angiographic contrast using single acquisition without subtraction. Although developed for renal angiography for its first application, VS‐MRA has shown great promise for peripheral, cerebral, and pedal angiography as well …”
Section: Introductionmentioning
confidence: 99%
“…Although developed for renal angiography for its first application, VS-MRA has shown great promise for peripheral, cerebral, and pedal angiography as well. 1,2,[8][9][10]…”
mentioning
confidence: 99%
“…Gold standard investigation for the patency of the pedal arch is operative angiogram, however, in patients where renal function is a concern VS magnetisation-prepared nMRA has been described as a non-invasive, radiation and contrast free alternative to CT/operative angiogram. It provides an excellent preview of the anatomy pre-operatively without compromising renal function 14…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] Recent studies on this technique (hereafter termed VS-MRA) have shown great promise for diverse arterial territories including renal, peripheral, cerebral, and pedal arteries. 21,22,25,26 This study aimed to evaluate image quality and diagnostic performance of unenhanced VS-MRA in PAD patients with DSA as the reference standard.…”
mentioning
confidence: 99%
“…This is superior to the subtractive 3D techniques, which require subtraction between flow‐suppressed and baseline images . Recent studies on this technique (hereafter termed VS‐MRA) have shown great promise for diverse arterial territories including renal, peripheral, cerebral, and pedal arteries . This study aimed to evaluate image quality and diagnostic performance of unenhanced VS‐MRA in PAD patients with DSA as the reference standard.…”
mentioning
confidence: 99%